The Use of Transthoracic Echocardiography in Caesarean Section Surgical Patients in the Intensive Care Unit: A Retrospective Cohort Study. Issue 4 (21st December 2022) - Smith, B.; Dennis, A.; Davies, K.; Cramp, P.; Gregory, K.; Sturgess, D.
Abstract : ( Aust N Z J Obstet Gynaecol . 2022;62:155–159) During pregnancy, cardiovascular changes can cause previously unknown cardiac pathologies to become life-threatening. Transthoracic echocardiography (TTE) can be used for identifying cardiac lesions, though there is little data of its use in high-risk postcesarean patients. This retrospective study analyzed TTEs in postcesarean patients in the intensive care unit (ICU), aiming to identify indications for TTE referral, examining the findings from TTE, and assessing whether these findings would have impacted anesthetic decisions had they been known preoperatively.